2014
DOI: 10.1177/1071100714549191
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Rates of Union and Hardware Removal Between Large and Small Cannulated Screws for Calcaneal Osteotomy

Abstract: Level IV, retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Our rate of removal of hardware is lower than that reported in the literature, which has shown removal rates of hardware due to prominence/irritation between 6% and 50%. 1-3,8,9 As previously mentioned, numerous studies have correlated high rates of removal with the use of screws, particularly headed screws, for fixation of calcaneal osteotomies. 1,3 Our hardware removal rate was low even when compared with studies that evaluated the rates of removal of lateral plates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our rate of removal of hardware is lower than that reported in the literature, which has shown removal rates of hardware due to prominence/irritation between 6% and 50%. 1-3,8,9 As previously mentioned, numerous studies have correlated high rates of removal with the use of screws, particularly headed screws, for fixation of calcaneal osteotomies. 1,3 Our hardware removal rate was low even when compared with studies that evaluated the rates of removal of lateral plates.…”
Section: Discussionmentioning
confidence: 99%
“…Hardware irritation leading to subsequent removal of the implant is common, and reported removal rates are high in the literature, ranging from 6% to 50%. 1-3,8,9 One recent study by Abassian et al 1 compared 3 different methods of calcaneal osteotomy fixation: a lateral locking plate, a headless screw, and a headed screw. They reported that 47% of the headed screws, 11% of the headless screws, and 6% of the lateral plates were removed to address symptoms from the hardware.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 There are various types of fixation used in MCO, but regardless of method, union rates after MCO are high, with studies reporting rates up to 97% to 100% with comparable rates of return to activity, hardware removal, and functional outcomes. 1,73,105,107…”
Section: Hindfoot Valgusmentioning
confidence: 99%
“…Currently, there is little research concerned with studying the effectiveness of different implant types that may be utilized during calcaneal osteotomy. A study by Sayres et al 7 demonstrated that the use of smaller-caliber cannulated screws resulted in fewer postoperative revision procedures (screws were removed because of patient complaints of pain and discomfort) relative to larger-caliber cannulated screws. Abbasian et al 1 similarly demonstrated that the rate of screw removal was significantly higher in patients receiving headed screws as opposed to headless screws, but the sample size was much smaller than the one presented in this study.…”
Section: Discussionmentioning
confidence: 99%